Permanent cell lines established from ts-COS cells that regulate by temperature the amplification and expression of cloned genes. - de la Luna, S (1987)
Temperature-sensitive COS cells have been transformed at restrictive temperature with SV40 replicons containing the neo or pac markers. Puromycin-resistant cell clones maintained at the restrictive temperature contain the pac gene integrated into the cell DNA. However, when the cells are shifted to the permissive temperature the pac gene is amplified in episomal forms up to 2-4 X 10(4) copies per cell. Concomitant with this, an induction of 35-300 fold in the levels of puromycin acetyl transferase activity is observed, leading to the accumulation of the enzyme up to 10-60 mU/mg of total cell protein. A band of apparent molecular weight 26,500 daltons is observed by polyacrylamide gel electrophoresis of induced culture extracts, that accounts for approximately 3% of the newly synthesized protein. The expression of non-selectable genes can also be regulated, as shown by the induction of influenza virus nucleoprotein synthesis in transformed cells. These results indicate that the ts-COS cells can be used as a highly efficient, regulable mammalian expression system.